Hubungan Pengetahuan Perioperatif dengan Tingkat Kecemasan pada Pasien Pre Operasi Katarak di RSU Bhakti Asih Tangerang - Ayu My Lestari; Any Kurniawati; Adin Syaefudin; Dwi Retno Handayani (Pusat Riset dan Inovasi Nasional, 2024)
Cataract is an eye disorder that occurs due to changes in the lens of the eye that is clear and translucent which can reduce the ability of vision to blindness. Cataract surgery is one of the most effective methods for cataract treatment. This study aims to determine the relationship between perioperative knowledge with anxiety levels of pre cataract surgery patients in RSU Bhakti Asih Tangerang. This research was conducted at RSU Bhakti Asih Tangerang with the research design used in this study being descriptive analytical using the cross-sectional method. The population in this study were pre-cataract surgery patients at RSU Bhakti Asih Tangerang who underwent surgery in October 2024, namely 120 patients and the sample used was 60 patients with a sampling technique using purposive sampling. The results of the Spearman's Rho test showed a significant negative correlation between perioperative knowledge and patient anxiety levels, with a coefficient of r = -0.610 and p-value = 0.000. This finding indicates that the better the perioperative knowledge a patient has, the lower the level of anxiety they feel before cataract surgery. The results of this study can be considered by health workers to help improve patient perioperactive knowledge such as holding seminars or webinars, distribution of educational pamphlets, so that the level of anxiety experienced by preoperative patients decreases.